Athletic expatriation and volleyball: adaptation to the new club - Tertuliano, Ivan Wallan; Machado, Afonso Antonio; Oliveira, Vivian de; Montiel, José Maria; Bartholomeu, Daniel; Deutch, Silvia (Manual Therapy, Posturology & Rehabilitation Journal, 2018)
Background: The expatriation of athletes occurs, most of the time, without proper preparation, which may compromise the athlete’s adaptation to the new work club. In this way, understanding the factors that can help in this process becomes necessary, because one can plan interventions to improve the athlete’s adaptation. Objective: To analyze the adaptation of the Volleyball athletes after changing to a new club and city to continue their career in the national and the international context. Methods: The sample was composed of 68 people (48 athletes and 20 ex-athletes), being 43 males and 25 females with mean age of 27 years. Participants were divided into 2 groups: G1 (International Athletes) and G2 (National Athletes). It was used a questionnaire with structured questions called “Questionnaire: the process of expatriation of volleyball players” and only the questions that were related to the objective of the study were used. The analysis of the results was conducted through analysis between groups and intragroup. Results: Both groups showed good adaptation to the new club, very influenced by the relationship with the athletes, coach and technical committee. Conclusions: The participants demonstrated adequate coping strategies and personal resources. In addition, it can be speculated that for an adequate adaptation to the new club, athletes must present adequate resources to face this new reality, demonstrating the need to prepare the athletes before the expatriation process.